Diagnóstico y diseño de estrategias comunicacionales para la protección de animales domésticos y de compañía, en el barrio de la Villaflora de la ciudad de Quito. - Arteaga Arévalo, Amanda Lizeth (2014)
This academic proposal presents a process of social research for animal protection. This work was done in the district with the Villaflora participation and members of the Central Committee. From the information obtained about keeping dogs and cats that live in this area, we worked on the design of communication strategies to raise awareness among residents on the care and protection of these animals. At present, is evident a greater focus on this issue by the public. It can be for fashion or for expansion of social consciousness that people discuss the irresponsible management of urban fauna that is kept in Quito, and the dangers that this brings to society. From a public health perspective, aesthetics, tourism and culture, actions of neglect, illegal reproduction and marketing are no longer unknown, or indifferent.